Development of a customs-integrated warehouse management system for inbound and outbound goods monitoring - Tri Handayani; Mustazzihim Suhaidi (Institute of Computer Science (IOCS), 2026)
The growth of international trade and customs-related logistics activities has increased the complexity of warehouse operations, particularly in managing inventory, inbound and outbound transactions, and customs document administration. This study aimed to develop a Customs-Integrated Warehouse Management System (CI-WMS) for monitoring inbound and outbound goods in customs-regulated warehouse environments in Dumai. The system was developed using the System Development Life Cycle (SDLC) based on the Waterfall model, which consists of requirements analysis, system design, implementation, and testing stages. The proposed system integrates product management, importer management, customer management, warehouse management, inbound and outbound transaction processing, customs document administration, and reporting functions within a centralized web-based platform. Functional testing was conducted to evaluate the performance of each system module based on predefined requirements. The testing results demonstrated that all modules operated successfully and produced valid outputs. The developed CI-WMS improves inventory visibility, supports inbound and outbound monitoring, enhances goods traceability, and facilitates customs document management within a single integrated system. The proposed system contributes to improving operational efficiency and supporting customs compliance in warehouse operations.